Bimbingan Penulisan Artikel Bagi Mahasiswa UIN Ar-Raniry dan Universitas Teuku Umar pada Harian Serambi Indonesia - Muzakkir Muzakkir; Said Fadhlain; Murhaban Murhaban; Teuku Farizal; Ikhsan Ikhsan; Alisman Alisman (Universitas Teuku Umar, 2022)
The importance of guidance on writing scientific articles for students which is carried out based on field research and analysis, in order to improve their competence as campus people. The purpose of this service is to understand and have the ability to write scientific papers for students of UIN Ar-Raniry and University of Teuku Umar (UTU). This guidance is carried out on the basis of students' lack of ability to produce scientific articles that can inspire the public. The advantages that can be obtained from these contributions are considered to arouse talent, interest, and enthusiasm as well as the enthusiasm of academic people to work. After conducting guidance on student productivity as an effort to develop intelligence to produce written works, also at least students are increasingly motivated to work to realize the ethics and personality of insightful undergraduates on campus. In this condition, it was seen that the guidance students (participants) were very enthusiastic about carrying out the assignments given by the resource persons. The assignments and exercises given complete the scientific articles of each participant. Enriching scientific knowledge in the form of articles for journals and books as a standard for a university graduate.